Assessment of Depression among the Housewives of Alcohol Consuming Husbands in Selected Community Areas, Kancheepuram District, Tamilnadu (Medico Legal Update, 2020)
Assessment of depression among the housewives of alcohol consuming husbands in selected communityareas, Kancheepuram District, Tamil Nadu. Aim of the study is to Assessment of depression among housewives. The objectives are to determine the level of depression among house wives of alcohol consuminghusband, to find out the association between the level of depression with their selected demographicvariables of the house wives of alcohol consuming husband.169 samples are selected by purposive samplingtechniques. Data collected by using Beck’s Depression scale.The data collected period was for one week. The collected data was tabulated and analyzed. Descriptiveand inferential statistical were used. The results are majority 53% of house wives having depression andMinority 47% of house wives did not having depression.Assessment of demographic variables regard to Factors associated with the level of depression among thedemographic variables, Family type,family monthly income ,Frequency of consuming alcohol,Variableslike Age,Educational status of wife, Educational status of husband, Employment status of husband,Problemafter alcohol consumption,Physically abuse after consumption of those Demographic variables doesn’t hassignificant association.